2006
DOI: 10.1002/ar.a.20382
|View full text |Cite
|
Sign up to set email alerts
|

Dietary consistency and plasticity of masseter fiber architecture in postweaning rabbits

Abstract: Dietary consistency has been shown to influence cross-sectional area and fiber type composition of the masticatory muscles. However, little is known about the effects of dietary consistency on masticatory muscle fiber architecture. In this study, we explore the effects of dietary consistency on the internal architecture of rabbit masseter muscle. Because activity patterns of the rabbit chewing muscles show inter-and intramuscular heterogeneity, we evaluate if alterations in fiber architecture are homogeneous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Even though we speculated above that these zoological animals shared broadly similar diets in captivity, this remains unproven. Studies comparing rabbits fed different diets show that the group masticating the more obdurate diet increased their masseter mass without changes in fiber length (Taylor et al, 2006) as well as had larger muscle fibers (Kiliaridis et al, 1988). Our results do not point to either an evolutionary mechanism or a physiological response as the predominant contributing factor in the larger PCSA and enlarged jaw muscles of C. apella .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though we speculated above that these zoological animals shared broadly similar diets in captivity, this remains unproven. Studies comparing rabbits fed different diets show that the group masticating the more obdurate diet increased their masseter mass without changes in fiber length (Taylor et al, 2006) as well as had larger muscle fibers (Kiliaridis et al, 1988). Our results do not point to either an evolutionary mechanism or a physiological response as the predominant contributing factor in the larger PCSA and enlarged jaw muscles of C. apella .…”
Section: Discussionmentioning
confidence: 99%
“…These and all other linear measurements were taken with digital calipers to the nearest 0.01 mm. Fiber length and pinnation angle were measured for both muscles following Taylor and Vinyard (2004) and Taylor et al (2006). Depending on the size of the muscle, we sectioned the masseter and temporalis muscles along their lengths to produce a minimum of two and a maximum of five segments, each segment approximately 1.5 cm in thickness (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Once weaned, mammals ingest 'adult' food items (e.g. Watts, 1985;Tarnaud, 2004) and develop 'adult' jaw-adductor activity patterns (Herring and Wineski, 1986;Weijs et al, 1987;Herring et al, 1991;Iinuma et al, 1991;Langenbach et al, 1991;Langenbach et al, 1992;Westneat and Hall, 1992;Huang et al, 1994), with associated skeletal and soft-tissue responses to 'adult' jaw-loading regimes (Ravosa, 1991a;Ravosa, 1992;Ravosa, 1996;Ravosa, 1999;Cole, 1992;Biknevicius and Leigh, 1997;Vinyard and Ravosa, 1998;Taylor et al, 2006).…”
Section: Adaptive Plasticity and Degradation In Masticatory Tissuesmentioning
confidence: 99%
“…Employing this experimental design, a number of studies have observed changes in the phenotypic properties of the jaw muscles related to changes in masticatory function brought about by changing the ordinary hard diet to a soft one (Kitagawa et al, 2004;Taylor et al, 2006). It has been suggested that the changes in the jaw-muscle properties are signs of a structural adaptation caused by a reduction in the neuromuscular activity of the muscles involved (Miyata et al, 1993).…”
Section: Introductionmentioning
confidence: 99%